Feminist and stratification theories' lessons from the crisis and their relevance for post-Keynesian theory - Stephanie Seguino (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2019)
The many contributions of post-Keynesian economists to understanding the causes of the global financial crisis that began in 2008 could be enhanced by integrating the research by feminist and stratification economists. These groups have produced a body of work analysing trends in inter-group and intra-class inequality that led up to the crisis and theoretically inform how we assess the distribution of the negative effects of the crisis by class, race, and gender. Further, this body of work has assessed the potential for fiscal and monetary policy to promote greater equality while reducing intra-class competition and conflict.
Keywords: B5; E6; Z13; 330; stratification; post-Keynesian macro models; gender; race; fiscal and monetary policy